Implementation of Learning Management by Teachers for Students with Special Needs at SMK Negeri 1 Rantau Prapat Labuhan Batu - Hajjatul Maria Ulfa Dongoran; Yusuf Hadijaya; Neliwati (Journal of General Education and Humanities, 2025)
Inclusive education in vocational schools faces significant challenges, particularly in how teachers manage learning for students with special needs. This study aims to explore and describe: (1) teachers' ability in planning learning for students with special needs, (2) the implementation of learning in inclusive classrooms, (3) assessment practices applied to students with special needs, and (4) the extent to which teachers can adapt learning materials and evaluations to meet diverse needs. This research employs a qualitative descriptive approach, with data collected through interviews, observations, and documentation. The research subjects included the school principal, guidance counsellors, homeroom teachers, students with special needs, and regular students. The findings reveal that while teachers show initiative and commitment to inclusive practices, they face major obstacles due to the lack of differentiated curricula, formal assessment tools, and specific training on handling students with special needs. Positive practices include regular parent-teacher communication, informal assessments, and peer-group integration strategies. However, systemic policies or institutional resources do not support these efforts. These findings indicate the urgent need for structured training programs, adaptive instructional materials, and policy-level support to optimise inclusive education practices in vocational schools.